Multiscale Structural Model of Super Carbon Nanotubes (Journal of Fiber Bioengineering and Informatics, 2014)
Extraordinary mechanical properties in biological composites come from their hierarchical structuresand are well seen in bones, teeth, shells etc. Nature inspired knowledge could certainly help in thedesign of new nanostructured materials. The current study illustrates a multi-scale nanotube model forthe purpose of the structure of very large groups of carbon nanotubes (CNTs). Two different types ofcircular beam finite elements are used to shape bond stretching energy or to account for the potentialconnected to bond angle variation. Multiscale approach considers CNTs at a mesoscopic level throughchains of straight cylindrical segments, where mesoscopic force field describes the interactions among thesegment. Property dependence at the nanoscale results from the surface and bulk energies competition.
Keywords: Hierarchy; Super Carbon Nanotube; Numerical Model